Blockchain Technology in UAE Construction Projects - Benefits, Applications, And Challenges - Abuhalimeh, Dania Jamal (2023)
A Master of Science thesis in Construction Management by Dania Jamal Abuhalimeh entitled, “Blockchain Technology in UAE Construction Projects - Benefits, Applications, And Challenges”, submitted in April 2023. Thesis advisor is Dr. Sameh El-Sayegh and thesis co-advisor is Dr. Abdulrahim Shamayleh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).